(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Authentic materials— such as newspapers, podcasts, and TV shows immerse learners in the culture and context of the target language. This article explores the use of authentic materials in language learning, emphasizing their ability to expose learners to real-world language use rather than the simplified language typically found in textbooks, offers best practices for using authentic materials effectively. The article aligns the use of these materials with the Communicative Approach to language teaching, which prioritizes interaction and practical application. The advantages of using authentic materials are outlined in detail. However, the article also acknowledges the challenges of using authentic materials, particularly for beginners.